Probleme psihosociale la adolescenţii din familiile temporar dezintegrate [Articol] - Bolea, Zinaida; Beradze, Marina (CEP USM, 2007)
The migration of parents is a habitual phenomenon for Republic of Moldova and represent a modality to improve economic condition for many families. Those more affected by this phenomenon are children and adolescents. The Ministry of Education of Republic of Moldova estimate for September 2005 that 35.000 children are living without parents and 75.000 have a parent abroad. Researches in this field revealed that the migration of parents have a significant negative effect on children and adolescents. There is a erroneous idea that adolescents are not so much exposed to risk in case of migration of parents. In fact, they are vulnerable to different psychological problems: antisocial behavior, schools problems, addictive behavior, depression, problems related to professional orientation, the alcohol and drugs abuse, precocious sexual life.
Keywords: dezvoltarea psihosocială; psihologia familiei; migrație